Assessment of coronary slow flow and its implications - Ranjan, Rajeev; Das, Santanu; Haque, M. Azizul; Chatterjee, Pritam Kumar (International Journal of Research in Medical Sciences, 2022)
Background: CAG is seen as the gold standard for the diagnosis of epicardial coronary artery disease. The clinical significance of coronary microvascular dysfunction has not been given much attention as epicardial coronary artery disease. Coronary slow flow phenomenon is another independent entity which is less studied and treatment plan and prognosis are not yet established. The objective of this study was to provide better understanding about the presence and pathophysiologic significance of coronary slow flow phenomena in patients undergoing coronary angiography (CAG) for various indications by corrected TIMI frame count (CFTC) in vessels without any flow limiting disease. Methods: We measured CTFC in patients enrolled for CAG. We compared CTFC among different presentations and in different arteries. We also compared coronary slow flow phenomenon to normal flow in coronaries and its correlation to risk factors Results: We found that coronary flow was significantly slower in non-infarct related arteries (NIRA) in the setting of ST segment elevation myocardial infraction (STEMI) and non-ST segment elevation myocardial infraction (NSTEMI) with no obstructive epicardial lesion as compared to coronary flow in absence of acute myocardial infraction (AMI). Significant slow flow was present in NIRA in STEMI compared to NSTEMI. Similarly slow flow was noted in unstable angina compared to chronic stable angina patients. Predominantly involved vessel was left anterior descending artery (LAD). Conclusions: Coronary flow was slower in NIRA in the setting of STEMI and NSTEMI with no obstructive epicardial lesion as compared to coronary flow in absence of AMI.